Voice and Swallowing Dysfunction in Neurofibromatosis 2. (March 2018) - Best, Simon R.; Ahn, Julie; Langmead, Shannon; Dhillon, Vaninder; Hillel, Alexander T.; Akst, Lee M.; Blakeley, Jaishri O.
Objective: Neurofibromatosis 2 (NF2) is a neuro-oncologic condition that presents with bilateral vestibular schwannomas of the cerebellopontine angle (CPA). Voice and swallowing impairment can occur from direct involvement or compression of the vagus nerve or as the result of surgical excision of CPA tumors. The objectives in this study are to (1) assess the prevalence of voice and swallowing impairments and (2) analyze the effects of vagal dysfunction in patients with NF2. Study Design: Cross-sectional. Setting: Academic tertiary care center. Subjects and Methods: Patients at a neurofibromatosis center were mailed Voice Handicap Index and Sydney Swallow Questionnaire surveys. Stroboscopic, voice, and swallowing evaluations were performed for patients who elected to participate in screening exams. Results: There were high rates of self-assessed and objective voice and swallowing handicaps in this population. Fourteen of 40 (35%) patients had a self-assessed voice handicap, and 20 of 40 (50%) patients had a self-assessed swallow handicap. Vocal fold motion impairment (VFMI) was observed in 22 of 31 (71%) patients examined, with 27 of 62 (44%) possible vocal cords affected. Velopharyngeal insufficiency (45%) and piriform sinus pooling or residue (39%) were seen in a significant percentage of patients. There was a significant relationship between vocal cord motion impairment and CPA surgical intervention ipsilateral to the impairment ( P = .002). The presence of VFMI was strongly associated with voice ( P = .002) and swallowing ( P = .01) impact on quality of life. Conclusion: Speech and swallowing impairments are highly prevalent in patients with NF2, cause significant impact on quality of life, and are most commonly related to surgical interventions in the CPA region.